2012
DOI: 10.1093/nar/gks630
|View full text |Cite
|
Sign up to set email alerts
|

RORγ directly regulates the circadian expression of clock genes and downstream targets in vivo

Abstract: In this study, we demonstrate that the lack of retinoic acid-related orphan receptor (ROR) γ or α expression in mice significantly reduced the peak expression level of Cry1, Bmal1, E4bp4, Rev-Erbα and Per2 in an ROR isotype- and tissue-selective manner without affecting the phase of their rhythmic expression. Analysis of RORγ/RORα double knockout mice indicated that in certain tissues RORγ and RORα exhibited a certain degree of redundancy in regulating clock gene expression. Reporter gene analysis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(170 citation statements)
references
References 54 publications
8
162
0
Order By: Relevance
“…3a and b). On the other hand, in the additional PFL, the activator promotes the transcription of Rors (mammals) [109][110][111][112] or Pdp1 (Drosophila) [107], which upregulates the transcription of the activator (Figs. 3a and b).…”
Section: Robust Designs Of Interlocked Transcriptional Feedback Loopsmentioning
confidence: 99%
“…3a and b). On the other hand, in the additional PFL, the activator promotes the transcription of Rors (mammals) [109][110][111][112] or Pdp1 (Drosophila) [107], which upregulates the transcription of the activator (Figs. 3a and b).…”
Section: Robust Designs Of Interlocked Transcriptional Feedback Loopsmentioning
confidence: 99%
“…Although RORs and Rev-erbs recognize the same motifs, they have opposing transcriptional activities and in vitro studies have suggested that the expression of a common target is determined by the outcome of the competition between the two factors (Liu et al 2008;Takeda et al 2012). Comparing gene expression changes in livers of RORa/g double knockout mice at ZT22 (when ROR expression is normally high) with gene expression in Reverba knockout mice at ZT10 (when Rev-erba expression is highest), we found several examples of common targets of Rev-erba and RORs (Zhang et al 2015).…”
Section: Rev-erbs and Rors Coordinate The Clock By Competing At Cognamentioning
confidence: 99%
“…RAR-related orphan receptors (RORs) are transcriptional activators and recognize the same DNA targets as of Rev-erba (Forman et al 1994;Giguère et al 1994). In addition to active recruitment of NCoR/HDAC3, in vitro studies have suggested that Reverba also represses gene expression by competing with RORs for binding to shared elements (Takeda et al 2012).…”
mentioning
confidence: 99%
“…Interestingly, among the target genes with the highest BMAL1 chromatin binding strength, most are well studied circadian genes. The top 10 CLOCK⅐BMAL1 target genes include three core clock gene Per1, Per2, and Cry2 (8,9); three nuclear receptors Rorc, Nr1d1, and Nr1d2 involved in the core clock regulation (10,11), and three PAR domain bZIP transcription factors Dbp, Hlf, and Tef, which function as key genes in the output pathways (12). Only one gene remains uncharacterized, gene model 129 (Gm129), which encodes a novel protein with no predicted functional domains.…”
mentioning
confidence: 99%